Evaluasi Kenyamanan Jalur Pejalan Kaki Bagi Mahasiswa Pada Kawasan Universitas Syiah Kuala - Amira Fudla; Zya Dyena Meutia; Reza Maulana Haridhi (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2024)
Syiah Kuala University is the oldest state university in Aceh located in the capital city of Aceh Province with its main campus located in the student city of Kopelma Darussalam, Banda Aceh. A pedestrian path is a movement of people from one place to another.Evaluation of the comfort of the pedestrian path in the Syiah Kuala University area is based on the existence of several pedestrian areas that have been damaged, potholed and misused.